Gunsights : and forty lashes less one - Leonard, Elmore, 1925-2013 (William Morrow, an imprint of HarperCollins Publishers, 2018)
Gunsights: Together, Brendan Early and Dana Moon have tracked down Apaches and gunned down scalp hunters to become Arizona legends. But now they find themselves fierce adversaries in what newspapers are calling The Rincon Mountain War. Brendan and a gang of mining company gun thugs are dead set on running Dana and the "People of the Mountain" from their land. Which of these former friends-turned-foes will triumph in the end?